IRRIGATION APPLICATION DEPTHS AND POTASSIUM DOSES ON TOMATOES UNDER PROTECTED ENVIRONMENT IN SOUTHEAST BRAZIL - Kalungu, Jokastah Wanzuu; Monteiro, Rodrigo OtÃ¡vio CÃ¢mara; Folegatti, Marcos VinÃcius (REVISTA DE AGRICULTURA, 2013)
Modern irrigation water and nutrient management strategies improve crop yields and lead to optimum profits. The objective of the study was to evaluate effects of irrigation depths and potassium doses on production, quality and water use efficiency of tomato (Lycopersicon esculentum Mills) under protected environment condition. The treatments consisted of irrigation water levels equivalent to 50, 75, 100, and 125% of crop water requirement (CWR) with potassium doses of 208, 416 and 624 kg ha-1. A drip irrigation system was used for fertigation of potted DÃ©bora Plus tomato variety. Irrigation, potassium doses and its interaction with irrigation levels had significant effects on total, commercial and non commercial production. Marketable yields reached a maximum of 64.4 mg ha-1 at 416 kg ha-1 of potassium, produced at 75% CWR. This corresponded to an average irrigation rate of 4.72 mm day-1. Higher potassium dose of 624 kg ha-1 depressed total and commercial yields. Tomato fruit pH values were between 4.0 and 4.5 for all treatments, while the highest total soluble solids were 9.2%, found with irrigation level of 75% CWR. Maximum water use efficiency was 12.4 kg m-3 of applied water, also obtained at 75% CWR. An irrigation reduction of 25% CWR could hence optimize water resources and save significant water quantities through improved efficiency of water applications to the plant. Â